Resisting Digital Coloniality: Exploring Technology Innovation in Global South Countries for Social Transformation - Pasqa, M; Putri, Taqiya Arini (Candidate: Jurnal Sains Politik, 2024)
Globalization has initiated significant changes in countries of the Global South, especially in their response to 'Digital Coloniality', where corporations from the Global North control the dominance of digital resources. These countries are actively working against this control, striving to establish their presence in the digital world. A key focus of this resistance is avoiding new dependencies in the digital era, characterized by the Global North's control over data, echoing a form of digital post-colonialism. This research centres on the role of Global South startups in creating social transformation through innovative approaches, emphasizing sustainability and societal impact. These startups are not just business entities but critical agents transforming local communities. The study suggests increased collaboration between the Global North and South and supportive governmental regulations to encourage tech innovations with valuable social impacts. This research offers insights into the evolving role of startup contributions in digital innovation, highlighting their growing influence in shaping a more equitable technological landscape and resisting digital coloniality in the Global South. Â